2021
DOI: 10.1002/ange.202100672
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid Strength of Interfacial Metal Sites Drives CH3OH Selectivity and Formation Rates on Cu‐Based CO2 Hydrogenation Catalysts

Abstract: CH3OH formation rates in CO2 hydrogenation on Cu‐based catalysts sensitively depend on the nature of the support and the presence of promoters. In this context, Cu nanoparticles supported on tailored supports (highly dispersed M on SiO2; M=Ti, Zr, Hf, Nb, Ta) were prepared via surface organometallic chemistry, and their catalytic performance was systematically investigated for CO2 hydrogenation to CH3OH. The presence of Lewis acid sites enhances CH3OH formation rate, likely originating from stabilization of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
(31 reference statements)
0
10
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] Some studies implied that the catalyst's OH groups promoted reactant adsorption on catalysts to improve reactant conversion, whereas some studies suggested that OH groups occupied active sites of catalysts to prevent reactant conversion. [4][5][6][7][8][9][10] Moreover, most of the previous works explored the influence of catalyst's OH groups on heterogeneous catalytic reactions as a whole, and the exact roles of OH groups at different sites of catalysts in heterogeneous catalytic reactions have not been well distinguished yet. [5][6][7][8][9] Besides, traditional ways to prepare heterogeneous catalysts often involve calcination or/and H 2 -reduction at temperatures higher than 400 C at which OH groups can be easily destroyed.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10] Some studies implied that the catalyst's OH groups promoted reactant adsorption on catalysts to improve reactant conversion, whereas some studies suggested that OH groups occupied active sites of catalysts to prevent reactant conversion. [4][5][6][7][8][9][10] Moreover, most of the previous works explored the influence of catalyst's OH groups on heterogeneous catalytic reactions as a whole, and the exact roles of OH groups at different sites of catalysts in heterogeneous catalytic reactions have not been well distinguished yet. [5][6][7][8][9] Besides, traditional ways to prepare heterogeneous catalysts often involve calcination or/and H 2 -reduction at temperatures higher than 400 C at which OH groups can be easily destroyed.…”
mentioning
confidence: 99%
“…The OH groups on catalysts were key factors affecting CO 2 hydrogenation efficiency. [5][6][7][8][9][10] The OH groups on Ni/γ-Al 2 O 3 catalyst were proposed to be able to tune the reaction pathway of CO 2 hydrogenation, with formate formation preferred on Ni/γ-Al 2 O 3 without OH groups but CO formation more facile on Ni/γ-Al 2 O 3 with OH groups. 8 Ye et al reported that the OH groups on a Pd/In 2 O 3 catalyst changed a key intermediate of CO 2 hydrogenation from CH 3 O to H 2 COH, and thus vary the CH 3 OH selectivity in CO 2 hydrogenation.…”
mentioning
confidence: 99%
See 3 more Smart Citations